1996
DOI: 10.1111/j.1151-2916.1996.tb08081.x
|View full text |Cite
|
Sign up to set email alerts
|

Grain‐Size Dependence of Sliding Wear in Tetragonal Zirconia Polycrystals

Abstract: He, Y.J.; Winnubst, L.; Burggraaf, A.J.; Verweij, H.; van der Varst, P.G.T.; de With, G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 26 publications
2
62
0
Order By: Relevance
“…Such mechanism of material removal, along with the formation of ribbon shaped particles, has also been reported earlier for ZrO 2 . 38,39 The occurrence of these tribomechanical wear induced material removal appeared to be relatively suppressed for the MSSed ZrO 2 nanoceramics. Raman spectroscopy experiments revealed that in addition to the presence of characteristic t-ZrO 2 bands (located at 149, 255, 318, 464, 640 cm −1 ), characteristic bands for monoclinic ZrO 2 (located at 181, 337, 472, 560 and 634 cm −1 ) were also present in the Raman spectra obtained from the worn surfaces of the SSSed ZrO 2 (see Fig.…”
Section: Wear Mechanisms and The Relationship With Mechanical Propertiesmentioning
confidence: 97%
“…Such mechanism of material removal, along with the formation of ribbon shaped particles, has also been reported earlier for ZrO 2 . 38,39 The occurrence of these tribomechanical wear induced material removal appeared to be relatively suppressed for the MSSed ZrO 2 nanoceramics. Raman spectroscopy experiments revealed that in addition to the presence of characteristic t-ZrO 2 bands (located at 149, 255, 318, 464, 640 cm −1 ), characteristic bands for monoclinic ZrO 2 (located at 181, 337, 472, 560 and 634 cm −1 ) were also present in the Raman spectra obtained from the worn surfaces of the SSSed ZrO 2 (see Fig.…”
Section: Wear Mechanisms and The Relationship With Mechanical Propertiesmentioning
confidence: 97%
“…Latest works expose that microstructure and mechanical properties, such as grain size [12][13][14][15][16], porosity [17], hardness [18,19], fracture toughness [20], have strong effect on abrasive/sliding wear resistance of bulk ceramics and coatings under dry or lubrication circumstances. Among the reduction in the grain size of ceramics, their mechanical properties would be improved [21,22], which is helpful in improving the abrasive/sliding wear resistance of bulk ceramics and coatings [1,18,[12][13][14][15][16][17][18][19][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of a zirconia phase transformation prevents the formation of microcracks on the top surface, but weakens the grain boundaries at the subsurface layer because generates internal stresses that promote delamination and pullout, resulting in a decrease in wear resistance. 8,[10][11][12][13][14] The aim of the present investigation is to study the sliding wear of ZTA composites with a Y-TZP content ranging from 7 to 22 vol.% in order to evaluate the effect of the infinite cluster formed at the percolation threshold on the wear resistance of ZTA composites.…”
Section: Introductionmentioning
confidence: 99%